TRUNK BIOMASS ESTIMATION BY DIFFERENT METHODS IN A SUBTROPICAL FOREST - Balbinot, Rafaelo; Trautenmüller, Jonathan William; Caron, Braulio Otomar; Breunig, Fábio Marcelo; Lambrecht, Fernanda Raquel; Costa Júnior, Sérgio (Floresta, 2017)
The aim of the work was to estimate trunk biomass in a Deciduous Seasonal Forest by using direct and indirect methods. The data were obtained from seven 12 x 12 m plots, bringing to a total of 64 trees. Trunk biomass was determined by direct method and indirect methods which consisted of: 1) Real Volume (RV) of the trunk multiplied by the Weighted Average (WA) and Arithmetic Average (AA) of the specific basic mass of the wood species found, resulting in Real Volume for Weighted Average (RVWA) and Real Volume for Arithmetic Average (RVAA), and 2) by the Estimated Volume (EV) multiplied by WAand by AA, resulting in Estimated Volume for Weighted Average (EVWA) and Estimated Volume for Arithmetic Average (EVAA). The trunk biomass of the three plots determined by the direct method was 11,451 Kg. The indirect method that had the most similar to the real trunk biomass (TB) value result was the EVAA (13,142 Kg), and the one that showed the largest difference was the RVWA,which was estimated at 20,061 Kg. The t-test showed significant difference of trunk biomass for indirect methods that used the RV; and the methods that used the EV did not differ statistically. Key-words: Forest biomass; arboreal biomass; Decidual Stational Forest. Resumo Estimativa da biomassa do fuste por diferentes métodos em floresta subtropical. O trabalho teve como objetivo estimar a biomassa do fuste em um fragmento de Floresta Estacional Decidual Montana utilizando métodos diretos e indiretos. Os dados de biomassa foram obtidos de sete parcelas de 12 x 12 m, totalizando 64 árvores. A biomassa do fuste foi determinada pelo método direto e por métodos indiretos que consistiram em: 1º) Volume Rigoroso (VR) do fuste multiplicado pela Média Ponderada (MP) e Média Aritmética (MA) da massa específica básica da madeira das espécies encontradas, resultando em Volume Rigoroso para Média Ponderada (VRMP)e Volume Rigoroso para Média Aritmética (VRMA), e 2º) pelo Volume Estimado (VE) multiplicado pela MPe pela MA, resultando em Volume Estimado para Média Ponderada (VEMP) e Volume Estimado para a Média Aritmética (VEMA). O TB das três parcelas determinado diretamente foi de 11451 Kg. O método indireto que mais se aproximou da biomassa do fuste foi o VEMA (13142 Kg), e o que apresentou a maior diferença foi o VRMP que totalizou 20061 Kg. O teste t indicou diferença significativa da biomassa do fuste para os métodos indiretos que utilizam o VR; e os métodos que utilizaram o VE não diferiram estatisticamente. Palavras-chaves: Biomassa florestal; biomassa arbórea; Floresta Estacional Decidual.